Study on the Movement Characteristics of Sediment Body in Mountain Rivers under Excessive Sediment Supply Conditions - ZHOU Qihang; ZHOU Yinjun; JIN Zhongwu; LI Zhijing; NIE Ruihua; LIU Xingnian (工程科学与技术)
ObjectiveSediment supply is an important control on sediment transport and riverbed morphology. Influenced by earthquake, bank collapse, landslides or debris flows, the sediment supply process in mountain rivers has changed significantly, resulting in abrupt adjustment of riverbed and frequent sediment-related disasters. Up to the present, the movement characteristics of sediment body have mainly focused on the episodic sediment supply induced by landsides or debris flows, the bedload transport law and riverbed evolution in mountain rivers under variable sediment supply conditions are still unclear. During flash flood in mountain rivers, a large amount of sediment enters rivers in a short period of time, exceeding the transport capacity of the flow and leading riverbed aggradation and water level rising so as to increase the flood risk. The previous studies have rarely addressed the evolution of sediment body under such excessive sediment supply conditions, resulting in inadequate estimation of hazard impacts, human casualties and property losses in vulnerable areas, which cause significant challenges for the prevention and control of sediment-related disasters. Therefore, this paper conducted a series of experiments to study the movement characteristics and bed evolution under varying sediment supply conditions, and revealed the influence of sediment supply process, magnitude (i.e., mass), and texture (i.e., grain size distributions) of variable sediment supply on translation and dispersion of sediment body. The results of this study can provide theoretical and technical support for sediment-related disasters control and river government.MethodsAll experiments were conducted in a 10 m long, 0.6 m wide, and 0.8 m deep rectangular glass-walled water recirculating flume at the State Key Laboratory of Hydraulics and Mountain River Engineering, Sichuan University, China. The uniform sediment with the median grain size D50 = 3.6 mm and geometric standard deviation σg = 1.18 and the non-uniform sediment with D50 = 4.8 mm and σg = 2.54 were used in experiments. 12 test runs were conducted with a constant flow discharge and four sediment supply modes, including a constant sediment supply regime and three stepped variable sediment supply regimes. During experiments, the flow discharge was measured using a rectangular weir installed upstream of the flume inlet. The water level and bed profile of a 5.5 m long test reach downstream of the sediment feeder were recorded and measured every 0.5 m using webcams with transparent grid sheets on the glass wall of the flume with an accuracy of ±2 mm. After the bed was dry, the high-resolution digital elevation models (DEMs) were obtained using structure-from-motion (SfM) photogrammetry to analyze the evolution of bed elevation and bed morphology.Results and Discussions (1) For the uniform sediment supply and bed material, the channel had net deposition under the same sediment supply mass and different sediment supply process, the total mass of sediment deposition for each test was consistent and the averaged bed elevation also remained the same as that before sediment supply. However, there were some differences in bedforms (i.e., the aggradation and degradation areas) under different sediment supply conditions, which may be related to the randomness of particle movement and the inhomogeneity of sediment supply along the flume width. For the non-uniform sediment supply and bed material, the bed deposition in the upstream was stronger than that in the downstream, and the more the sediment supply, the greater the degree of bed aggradation. (2) For the constant sediment supply regime and stepped variable sediment supply regime, the sediment body presented a wedge shape, the longitudinal profile of sediment body shown a process of increasing and lengthening first, then decreasing and shortening, and finally stabilizing. According to the movement process of the mass center of sediment body, it can be seen that the trajectory of the mass center was clockwise during riverbed aggradation and degradation process, and the speed of aggradation was greater than that of degradation. (3) The sediment propagation form can be assessed based on the downstream cumulative difference of bed elevation (CED). The CED curve rotates clockwise and fades with time for dispersion, migrates to downstream entirely without any deformations for translation, and shows both a progressive translation to downstream and a rotational decline in the slope of the curve for the mixed dispersion and translation. The results of the current study shown that the sediment body propagates primarily though dispersion to downstream for uniform sediment supply and bed material. The relative dispersion and translation of the sediment body induced by excessive sediment supply can be further quantified by plotting the CED interquartile range (IQR, the length enclosing the central 50% volume) against the CED center location (i.e., the median of the CED curves). The slope of IQR against the center location ranges from 0.98 to 1.38 for uniform sediment tests, according to the previous studies, the sediment body primarily though dispersion to downstream. (4) According to the downstream cumulative distribution of elevation difference (CED) and the relationship of CED interquartile range and CED longitudinal center location, the movement forms of sediment body are divided into three intervals. For the large-fine and large-coarse sediment supply, the sediment body propagates primarily though dispersion to downstream. For the small-fine and small-coarse sediment supply, the deposited sediment propagates primarily through dispersion-translation to downstream.ConclusionsThe present study conducted a series of experiments to investigate the movement characteristics of sediment body in mountain rivers under excessive sediment supply conditions. The sediment supply process, sediment supply mass and sediment supply grain size distribution on the movement law of sediment body and the characteristics of riverbed evolution were revealed. The downstream cumulative difference of bed elevation (CED) and the CED interquartile range (IQR, the length enclosing the central 50% volume) against the CED center location can be used to assess the sediment propagation form of dispersion and translation. The results of this study can provide theoretical and technical support for sediment-related disasters control and river government.